The molecular cloning and differential expression of hepatitis B viral protein-encoding genes in the yeast Saccharomyces cerevisiae - Plüddemann, Annette,1972- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.